2016
DOI: 10.1080/08820538.2016.1208764
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Tear Film Lipid Layer Thickness after Cataract Surgery

Abstract: The tear film LLT was significantly thinner and DES and MGD parameters showed deterioration after cataract surgery. In addition, LLT was significantly correlated with DES and MGD parameters. These results suggest that clinicians should consider the tear film lipid layer while managing the exacerbation of DES after cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 30 publications
0
29
1
12
Order By: Relevance
“…It is known that Meibomian gland dysfunction and deterioration of the tear film may increase after cataract surgery [ 40 , 41 , 42 ]. However, the exact mechanism by which cataract surgery impairs the Meibomian gland function remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Meibomian gland dysfunction and deterioration of the tear film may increase after cataract surgery [ 40 , 41 , 42 ]. However, the exact mechanism by which cataract surgery impairs the Meibomian gland function remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al have reported abnormal meibomian gland function as the cause of dry eye related to cataract surgery 12 . In another study authors have found thinning of lipid layer after cataract surgery 13 . These changes in the pre-corneal tear film make it less stable leading to development of dry eye 14 …”
Section: Discussionmentioning
confidence: 99%
“…LipiView interferometry was applied to evaluate the tear film LLT and to monitor blinking patterns by capturing 20 s videos. The LLT results were converted from interferometric colour units into nanometres and the numbers of incomplete blinks and total blinks were calculated [14].…”
Section: Llt and Blinking Patternmentioning
confidence: 99%